2017
DOI: 10.1155/2017/6920904
|View full text |Cite
|
Sign up to set email alerts
|

Forecasting the Acquisition of University Spin-Outs: An RBF Neural Network Approach

Abstract: University spin-outs (USOs), creating businesses from university intellectual property, are a relatively common phenomena. As a knowledge transfer channel, the spin-out business model is attracting extensive attention. In this paper, the impacts of six equities on the acquisition of USOs, including founders, university, banks, business angels, venture capitals, and other equity, are comprehensively analyzed based on theoretical and empirical studies. Firstly, the average distribution of spin-out equity at form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…The choice of influencing factors has a significant impact on the prediction accuracy of the model. Most researchers in past studies [1][2][3][4][5][6][7] selected a number of factors as influencing factors of public budget revenue, including the number of employees in employment, total wages, total retail sales of consumer goods, fixed asset investment, resident consumption index, gross regional product, primary industry, secondary industry, and tertiary industry. In Li Min's study on the impact of fiscal revenue in Gansu Province [1], the largest number of factors was as many as 39 and the smallest number of factors was 5.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The choice of influencing factors has a significant impact on the prediction accuracy of the model. Most researchers in past studies [1][2][3][4][5][6][7] selected a number of factors as influencing factors of public budget revenue, including the number of employees in employment, total wages, total retail sales of consumer goods, fixed asset investment, resident consumption index, gross regional product, primary industry, secondary industry, and tertiary industry. In Li Min's study on the impact of fiscal revenue in Gansu Province [1], the largest number of factors was as many as 39 and the smallest number of factors was 5.…”
Section: Introductionmentioning
confidence: 99%
“…Peng Qin [3] used minimum angle regression to solve the adaptive Lasso estimation, which eliminates some covariates and variables with small effects. Peiyu Liu [4] used lasso and random forest for variable screening, respectively. Yang He [5] demonstrated that lasso regression has great advantages in the variable selection process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome some shortcomings in the aforementioned methods for the battery pack SOC estimation, this paper presents an improved RBF method using a fast recursive algorithm (FRA) to estimate the SOC of a battery pack. e FRA method [27] can be used for both neural inputs selection [28] and hidden layer node selection [29][30][31] in the configuration of RBF networks. Comparing to [32], the average cell temperature, the time mean pack voltage, the time mean pack temperature, and the time mean loop current all over 10 seconds intervals can be also added to the initial candidate pool of input variables, other input candidates can also be included such as the maximum cell voltage, the minimum cell voltage, the average cell voltage, and loop current.…”
Section: Introductionmentioning
confidence: 99%